(untitled) (Хабаршы. Психология және социология сериясы, 2024)
The purpose of the scientific article is to evaluate the concept of psychological capital as a factor of employee effectiveness and, as a result, the productivity of the entire company as a whole. The following methods of information collection were used in the article: analysis of literature sources on the problems and methods of assessing the psychological health of personnel; review of scientific articles on the problem of personnel assessment; methods of comparative analysis and synthesis. Psychological capital can be considered not only as a precursor to productivity, but also as a harbinger of mental health in the workplace. Thus, an increase in psychological capital in organizations would allow for "win-win" events for both parties involved (employers and employees). The results obtained in this work may encourage HR managers to focus more on psychological capital, as the development of self-efficacy, hope, optimism and resilience is crucial for the formation of desirable organizational attitudes and behaviors. At the same time, the main advantage of the four dimensions of psychological capital is that these dimensions are psychological quasi-states, which, unlike traits and quasi-traits, can be developed and can be "important assets for development". Key words: psychological capital, psychological resources of employees, labor psychology, productivity, efficiency.